Exploiting nonlinearity to improve the effectiveness of a vibration neutralizer - Gatti, G.; Brennan, M. J. [UNESP] (My University, 2012)
This paper present a study on the use of geometric stiffness nonlinearity to improve the effectiveness of a vibration neutralizer attached to a machine subject to harmonic excitation. It is assumed that the machine acts as a simple mass, the frequency of excitation is well above the resonance frequency of the machine, and the response of the system is predominantly harmonic at the frequency of excitation. It is shown how the nonlinearity has the effect of shifting the resonant peak to a higher frequency away from the tuned frequency of the neutralizer so that the device is robust to mistune. In a linear neutralizer this can only be achieved by adding mass to the neutralizer, which may be undesirable. It is also shown how the nonlinearity has the effect of increasing the bandwidth of the device compared to the equivalent linear neutralizer. Approximate expressions are derived, which facilitate insight into the parameters which affect the system dynamics, and an experimental work is conducted to validated the theoretical findings. © (2012) by the Katholieke Universiteit Leuven Department of Mechanical Engineering. All rights reserved.